ANALISIS KEJADIAN TB PARU BERDASARKAN LINGKUNGAN DI DESA KEDUNGREJO KECAMATAN MUNCAR BANYUWANGI - Sasongko, Hendrik Probo; Nanda, Febrika Devi (Universitas Muhammadiyah Jember, 2017)
Tuberculosis is one of the existing disease problems in Indonesian. The incidence of TB in Kedungrejo Village Muncar District was 26 cases. This study aims to determine the incidence of TB based on the environment and efforts to control the incidence of TB in Kedungrejo Village Muncar District. The type of this research was observational analytic used survey method and questionnaires with case control approach. Samples in this research were 52 Respondents. Sampling technique used simple random sampling. Data analised with chi square test at 95% confidence level using SPSS version 23.0. Result of research indicate there were relation between environment with incidence of TB in Kedungrejo Village Muncar District Banyuwangi, chi square statistic test result show that p = 0,01 (p<0,05). The conclusion in this research was there is a statistical relationship between environmental with TB incidence in Kedungrejo Village Muncar District BanyuwangiKeywords: Tuberculosis, environment